Impact of Using Cognitive Technology in Increasing the Efficiency of the Learning Process - Baso Intang Sappaile (Journal Emerging Technologies in Education, 2024)
Background:Utilizing cognitive technology has significantly improved educational outcomes, with a real impact on the effectiveness of the learning process.Cognitive technology allows teachers to present lesson content that is aligned with students' level of understanding and learning styles, resulting in more effective and efficient teaching. The use of cognitive technology not only increases the efficiency of the learning process but also creates a more thoughtful and focused learning environment for students. Research purposes:ObjectiveThis research aims to determine the impact of using cognitive technology in increasing the efficiency of the learning process. As well as knowing the effect of using cognitive technology which can increase efficiency in the learning process. So that the desired learning objectives are achieved. Method:This research uses quantitative methods so that it can provide data in the form of accurate numbers. Data was obtained by distributing an online questionnaire via the Google Form application to respondents. The respondents' results will be managed using the SPSS application. After data management, researchers present the data in the form of graphs or diagrams. Results:From the results of this research, it can be seen that cognitive technology has a significant impact in increasing the efficiency of the learning process. By using cognitive technology that can be accessed anytime and anywhere, it can make it easier for students to understand the material. So as to create an efficient learning process. Conclusion:From this research, researchers can conclude that the impact of using cognitive technology can increase efficiency in the learning process. So as to create a safe and comfortable learning atmosphere. And achieving the desired learning goals.